Assessing the impact of the wildlife trade in West Africa (Benin): Functional diversity matters too - (:unkn) unknown (My University, 2023)
We tackle the potential impact of bushmeat markets (BM) and traditional medicine markets (TMM) on the functional diversity of mammalian communities in southern Benin, West Africa. A hybrid approach combining direct observations, DNA-typing and questionnaires allowed us to identify 94 species-level taxa across 11 mammalian orders, the greatest ever reported numbers for African wildlife markets. TMM sold species of high conservation concern or regulated by international conventions and sourced among all the taxonomic orders and bioclimatic zones of the country. BM were taxonomically and functionally 100% nested within TMM. However, functional richness was high in both markets, impacting nine diet specializations and five ecological functions, which included seed dispersion (frugivores, folivores and omnivores), prey regulation (carnivores and invertivores), browsing (folivores), grazing (omnivores) and fertilization (nectarivores). TMM likely jeopardized the regulatory, structural and production functions of the sourced ecosystems as they sold species with the greatest body weights and generation lengths, and smallest litter sizes, including large herbivores and keystone predators. BM, despite their restricted range, sourced among a non-selective taxonomic and functional spectrum and as such, also represent a significant threat to ecosystem functioning in southern Benin. The functional database that we provide can serve as a starting point to pursue the quantification of functional diversity in African mammals and further investigate the impact of wildlife markets on ecosystem functioning in tropical Africa. Overall, long-term surveys of the two types of wildlife markets are needed to accurately quantify the threat they constitute to mammalian biodiversity and the sustainability of ecosystem services.
Keywords: African Research